IMPLEMENTASI KETERBUKAAN INFORMASI PUBLIK MELALUI SISTEM INFORMASI MANAJEMEN PENDIDIKAN (SIMPENDIK) DI DINAS PENDIDIKAN KOTA SEMARANG - Jasrianto, Dori; Taufiq, Ahmad; Sulistyowati, Sulistyowati (Journal of Politic and Government Studies, 2015)
Public information disclosure is an aspect which is inseparable in the life of a democracy, where the rights of the individual over the public information must be fulfilled. To encourage the expansion of public information thoroughly, then every public institution is required to make asystem information which can be accessed quickly and easily by the public.Responding to the issue, Semarang City Education Office seriously launched management information systems education (SIMPENDIK) as a tool of information expansion, in cooperation with DINUSTEK and TELKOM Indonesia. This policy is Derivet (Derivative Policy), which is based on Act No. 14 of 2008 on public disclosure, as well as the regulation of the derivatives: Semarang Mayor Decree No. 821.29/265 on Information and Documentation Management Officer (PPID) in Semarang municipal government’s environment, and Perwal No. 26 in 2012on guidelines for information and documentation management. The purpose of this research is to find out the implementation and the driving factor, as well asthe inhibitor to the implementation of the public information disclosure through the education management information system (SIMPENDIK) in the Semarang City Education Office. Research methods used in this research are Descriptive-analytic methods. To answer the research problems, the author uses George c. Edwar III’s theory, i.e. communication, resources, disposition, and bureaucratic structure.The results of the research shows that the disclosureof public information through the education management information system (SIMPENDIK) in the Semarang City Education Office is already doing well, though there are still obstacles present, such as the lack of socialization to society, the limited number of personnel on Officer Functional information, the absence of a special room for the information manager, and the lack of a specific budget to support the implementation of the public information disclosure, as well.